The Rising Incidence of Skin Cancers in Young Adults: A Population-Based Study in Brazil - Joseph Jose Flavio; Sarah Fernandez (Scientific Journal of Dermatology and Venereology, 2025)
Introduction: Skin cancers, historically associated with older populations, are increasingly affecting young adults. This study investigates the incidence trends of skin cancers among young adults (18-39 years) in Brazil, a country with high UV exposure and diverse skin types. Methods: A population-based retrospective study was conducted using data from Brazil's National Cancer Registry (INCA) between 2010 and 2023. Incidence rates were calculated for melanoma, basal cell carcinoma (BCC), and squamous cell carcinoma (SCC) among young adults, stratified by age, sex, and region. Joinpoint regression analysis was used to assess temporal trends. Results: A total of 12,560 skin cancer cases were identified in young adults. BCC was the most common (55%), followed by SCC (30%) and melanoma (15%). Overall incidence rates increased significantly for all skin cancer types, with an average annual percentage change (AAPC) of 3.2% for BCC, 2.8% for SCC, and 4.5% for melanoma. The highest incidence rates were observed in the Southern region, followed by the Southeast. Females had a higher incidence of melanoma, while males had a higher incidence of BCC and SCC. Conclusion: This study demonstrates a concerning rise in skin cancer incidence among young adults in Brazil. The findings highlight the need for targeted prevention efforts, including sun protection education and early detection programs, to address this growing public health issue.